Building A Christian Education Paradigm In The Era Of Globalization: An Examination Of Educational Philosophy And Its Implementation In Bee Discipleship - David Samuel; Stefanus Dully; Bong, Hae Nam; Nik Anna (LPPM Universitas PGRI Sumatera Barat, 2025)
The era of globalization has bring change big in all over aspect life humans, including in field education and life church. Technological changes, the flow of information, and value pluralism pose new challenges in maintaining the faith and spiritual growth of Christians. Christian education, which was once more traditional and institutional, is now required to be able to present a contextual, relevant, and transformative approach. One prominent model is approach BEE (Biblical Education by Extension) discipleship which has philosophy “knowing, being, doing” service philosophy This emphasize the need equip students with knowledge Bible (know), formation character Christ (be), and expertise serve (do) so that they capable become God's faithful servant in the middle challenges of the times. This article uses a qualitative approach using literature review and conceptual analysis of the philosophy of Christian education and the practice of BEE discipleship. The main objective of this article is to develop a relevant Christian education paradigm in the era of globalization by emphasizing the importance of integrating cognitive, affective, and psychomotor aspects in discipleship. This article finds that the biblical philosophy of Christian education is grounded in the goal of Christ-likeness, and its implementation in the BEE model can be a strategic alternative for the contemporary church